Development Process of Banking Regulations in Turkish Legal System - Yasam Demir; Sebnem Yalcin (European Scientific Journal, ESJ, 2017)
The regulation of banking sector recently has become one of the discussed issues after the crisis experienced in developed and developing countries. The opinion that the international regulations and standards are not enough for the surveillance and audit of the banks, has began to prevail. In this aspect, the regulations, which every country has done in the scope of internal dynamics, took attention. In this study legal regulations that Turkey, where the negative effects of 2008 crisis are seen relatively less than European countries, has besides having international banking standards are analyzed. The development process of Banking Law is examined in respect to the historical process.